Urban Retail Patterns Of Penang Road And Campbell Street - Chong, Pit Kuen (Pusat Pengajian Ilmu Kemanusiaan, 1982)
In recent years, urban development in Central George town has been concentrated only in certain parts of the area, and not evenly spaced out. Urban developments are seen in the form of the proliferation of supermarkets and departmental stores as well as in the uprising of the New Urban Centre Project. Su permarket are mainly concentrated in Burmah Road, where, since mid-I9?0's, four such unite have been built in that area.